Efficacy of biological agents and fillers seed coating in improving drought stress in anise - Hoseini, Atefeh; Salehi, Amin; Sayyed, R. Z.; Balouchi, Hamidreza; Moradi, Ali; Piri, Ramin; Fazeli-Nasab, Bahman; Poczai, Peter; Ansari, Mohammad Javed; Obaid, Sami Al; Datta, Rahul (Frontiers in Plant Science, 2022)
Many plants, including anise, have tiny, non-uniform seeds with low and light nutrient reserves. These seeds also show a weak establishment, especially in stressful conditions where their accurate planting in the soil and optimal yield are tough. This study attempted to improve anise seeds' physical and physiological characteristics under drought stress. To this end, two factorial experiments were performed in a completely randomized design with 4 and 3 replications, respectively, in laboratory and greenhouse conditions. Five levels of seed inoculation (inoculation with T36 and T43 of Trichoderma harzianum, and CHA0 and B52 of Pseudomonas fluorescent, and Non-inoculation), three levels of coating (K10P20, K10P10V5, and Non-Coating), and three levels of drought stress (0, -3 and -6 bar) were considered as the factorial experiment (Vermiculite=V, Kaolin=K, and Perlite=P Numbers refer to the amount of material used in terms of grams). The laboratory experiment revealed that the combined treatments of bio-agents with coating increased the physical and germination characteristics of anise seeds compared to the control treatment. Besides, the greenhouse experiment showed that the drought stress reduced the initial growth indices. Still, the combination treatments of biological agents and coating (fillers) could alleviate the destructive effects of drought stress to some extent and improve these indices. The best treatment was allocated to a T36 and K10P20 treatment in both experiments, which significantly increased morphological indices.